Submitted to the Select Committee on Dying with Dignity - The English Speaking Catholic Council (ESCC) (2010)
In 1980, a group of individuals who represented various sectors of the English-speaking Catholic community and its organizations met with the idea of consolidating our human and material resources for the development of our community. This led to the formation in 1981 of the English Speaking Catholic Council (ESCC) with a mandate to act as a focal point in coordinating the English-speaking Catholic community of Greater Montreal. Over the years, the ESCC has assumed a higher profile which now extends throughout the Province and beyond. Inspired by the contemporary Catholic understanding of the role of the laity in the modern world, the English Speaking Catholic Council assists in the promotion of its community’s values and advocates those values in the resolution of issues affecting this community. The Board of Directors is made up of women and men from both the private and public sectors, all volunteers, who come together with a commitment to support their community in education, health and social services, community animation, culture and social justice.

Soumis au Comité spécial Mourir avec Dignité par Le conseil catholique d’expression anglaise - The English Speaking Catholic Council (ESCC) (2010)
En 1980, nous, un group d’individus représentant divers secteurs de la communauté Catholique anglophone et ses organisations, nous sommes réunis dans le but de consolider nos ressources humaines et matérielles, en vue du développement de notre communauté. Cela a mené, en 1981, à la création du Conseil catholique d’expression anglaise (CCEA), ayant le mandat d’agir comme point central dans la coordination de la communauté Catholique anglophone de la région urbaine de Montréal. Au cours des ans, l’CCEA a assumé un rôle plus proéminant, élargissant son activité à toute la province et au-delà. S’inspirant de la compréhension Catholique contemporaine du rôle de la communauté laïque dans le monde moderne, Le conseil catholique d’expression anglaise aide à promouvoir les valeurs de sa communauté, et défend ces valeurs dans le processus de résolution des problèmes ayant un impact sur cette communauté. Le conseil d’administration se compose d’hommes et de femmes du secteur public et privé, tous bénévoles, qui s’engagent à appuyer leur communauté dans les domaines de l’éducation, de la santé et des services sociaux, de l’animation sociale, de la culture et de la justice sociale.